Saúde bucal e qualidade de vida relacionada à cárie dentária em escolares de 08 a 10 anos de idade de um município paulista - Vilela, Viviane Rodrigues (2016)
This study aimed to analyze the association between quality of life and oral health of children from eight to ten years old. It is a cross, quantitative research with descriptive characteristics among 102 students from a primary school of São Paulo state. The study was approved by the Research Ethics Committee. Dental Caries was measured by the DMFT and dmft index. The risk of caries was classified by the instrument developed by the Health Department of São Paulo. The quality of life by self-perception of oral disorders was verified using the CPQ 8-10 questionnaire. The results identified an average DMFT of 1.50 and dmft of 2.37. For classification of the risk of caries disease, absolute and relative frequencies were used, noting 22 (21%) of the study subjects who had low risk of caries disease, 12 (12%) moderate risk, and most with 67 children (67%) presented high risk for caries. Kendall correlation test found the degree of association and estimation of variables among the scores of quality of life and risk of caries disease, indicating a positive and significant correlation. To compare the average score among the three risk classes it was applied the analysis of variance (ANOVA) test. The average scores were 9.82; 24.58 and 54.68 for the risk class "low", "moderate" and "high" respectively. Through ANOVA it was also observed association between the risk of tooth decay and quality of life scores, which means, the higher the risk the lower quality of life related to oral health. It highlights the importance and low cost given the risk of detection procedure to dental caries, because the high risk can have a negative influence on children's quality of life and affect their health and general well-being. In this sense, the overall health condition of the child is of crucial importance, being oral health also responsible for the set. It is recommended the development of qualitative studies, which would contribute to the deepening of the issue under review. Thus, the school space could be more used for the development of intersectoral actions as it is a promising scenario for building strategies that produce health in the light of health promotion.